Designing for Scale: Reflections on Rolling Out Reading Improvement in Kenya and Liberia. Issue 155 (March 2017) - Gove, Amber; Korda Poole, Medina; Piper, Benjamin
Abstract: Since 2008, the Ministries of Education in Liberia and Kenya have undertaken transitions from small‐scale pilot programs to improve reading outcomes among primary learners to the large‐scale implementation of reading interventions. The effects of the pilots on learning outcomes were significant, but questions remained regarding whether such large gains could be sustained at scale. In this article, the authors dissect the Liberian and Kenyan experiences with implementing large‐scale reading programs, documenting the critical components and conditions of the program designs that affected the likelihood of successfully transitioning from pilot to scale. They also review the design, deployment, and effectiveness of each pilot program and the scale, design, duration, enabling conditions, and initial effectiveness results of the scaled programs in each country. The implications of these results for the design of both pilot and large‐scale reading programs are discussed in light of the experiences of both the Liberian and Kenyan programs.